Chapter 4 Religious conflict, radicalism, and sexual exceptionalism in the rhetoric of John Chrysostom - Wet, Chris L. de (Taylor & Francis, 2018)
Relying on the works of Jasbir Puar and Marchal, the chapter explores the locus where sexuality, specifically the formation of masculinity, intersects with religious conflict, notably in the formation of late antique religious radicalism, using the homilies of John Chrysostom as a case in point. In a study engaging with religious conflict and notions of "just peace" in Augustine's thought, Serena Sharma highlights the importance of identifying, problematising, and addressing historical discursive grey zones. Inclusion is a very important feature in the operations of sexual exceptionalism and religious conflict. Two important strategies are at play in the sexual exceptionalism of religious conflict, namely inclusion, and teratogenisation. Chrysostom meticulously constructs the sexual perversity of his opponents in contrast to the sexual exceptionalism of his own group. The formation of masculinity in terms of sexual exceptionalism and perversity therefore has a leading role in religious conflict.